Flammability of sulfur powder - An extremely hazardous chemical. (March 2021) - Zeng, Zhe; Oluwoye, Ibukun; Altarawneh, Mohammednoor; Dlugogorski, Bogdan Z.
Abstract: This contribution investigates the propensity of low-temperature ignition of sulfur, a hazardous substance because of its facile flammability. We applied the coupled thermogravimetric analyser and differential scanning calorimeter (TGA-DSC), in conjunction with a vertically-entrained reactor, to study the ignition behaviour of sulfur powder. The thermogravimetric measurements capture the ignition temperature of sulfur powder that transforms itself to partly polymerised S8 phase (S γ ) prior to ignition, revealing a temperature as low as 480 K. Likewise, experiments performed in a vertically-entrained reactor, coupled with an online Fourier-transform infrared (FTIR) spectrometry confirm the ignition temperature of S γ of between 473 K and 483 K, as well as the full conversion of S into SO2 at 503 K. The density-functional-theory calculations for the S + O2 reaction identify the formation of SO + O as the initiation step, with a shallow activation barrier of 24.6 kJ mol −1 . Further oxidation of SO + O2 → SO2 + O proceeds slower with a relatively high activation barrier at 34.0 kJ mol −1, acting as the bottleneck step of oxidation of elementary S, in analogy to the DSC profile of S γ ignition . Highlights: Sulfur powder forms the partly polymerised and fused S8 (S γ ) prior to ignition. S γ ignites at temperatures as low as 480 K. The activation energy for oxidation of S γ amounts to 89.0 kJ mol −1 . Theoretical modelling identifies the ignition reaction as S + O2 .→ SO + O.